2023
DOI: 10.1038/s41598-023-40880-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of tuber-bound free amino acids in potato and effect of growing environment on the amino acid content

Jeewan Pandey,
Dalton Thompson,
Madhumita Joshi
et al.

Abstract: Free amino acids in potato tubers contribute to their nutritional value and processing quality. Exploring the natural variation in their accumulation in tubers across diverse genetic backgrounds is critical to potato breeding programs aiming to enhance or partition their distribution effectively. This study assessed variation in the tuber-bound free amino acids in a diversity panel of tetraploid potato clones developed and maintained by the Texas A&M Potato Breeding Program to explore their genetic basis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…As for other species, several studies have identified SNPs associated with agronomical and quality traits, such as tuber shape, eye depth, and fry color retention during low-temperature storage ( Sharma et al., 2018 ; Byrne et al., 2020 ; Zhang et al., 2022a ; Pandey et al., 2023 ; Zhao et al., 2023 ). Moreover, multiple genetic markers and candidate genes aimed at enhancing disease resistance to late blight have been identified by Wang et al.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%
“…As for other species, several studies have identified SNPs associated with agronomical and quality traits, such as tuber shape, eye depth, and fry color retention during low-temperature storage ( Sharma et al., 2018 ; Byrne et al., 2020 ; Zhang et al., 2022a ; Pandey et al., 2023 ; Zhao et al., 2023 ). Moreover, multiple genetic markers and candidate genes aimed at enhancing disease resistance to late blight have been identified by Wang et al.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have been used to dissect the genetic basis of traits in potatoes (Rosyara et al, 2016;Sharma et al, 2018). GWAS has been conducted in potatoes for protein content (Klaassen et al, 2019), scab resistance (Kaiser et al, 2020), root and stolon traits (Yousaf et al, 2021), tuber traits (Pandey et al, 2022), tuber bruising (Angelin-Bonnet et al, 2023), and tuber-bound free amino acids (Pandey et al, 2023b), etc. However, there has been no prior instance of GWAS for mineral content in potato tubers based on our knowledge.…”
Section: Introductionmentioning
confidence: 99%